2015
DOI: 10.1016/j.newast.2013.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Multiwavelength modeling the SED of supersoft X-ray sources. II. RS Ophiuchi: From the explosion to the SSS phase

Abstract: Physical parameters of the nova RS Oph were determined from its X-ray/IR spectrum. -The model revealed the presence of a strong stellar and nebular component. -The luminosity was super-Eddington during the whole burning phase. -The high luminosity was sustained by a super-critical accretion.Abstract RS Oph is a recurrent symbiotic nova that undergoes nova-like outbursts on a time scale of 20 years. Its two last eruptions (1985 and 2006) were subject of intensive multiwavelengths observational campaign from t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 44 publications
(59 reference statements)
2
8
0
Order By: Relevance
“…Mondal et al (2018) from the absorption band indices derived the spectral type to be M2-M3. Skopal (2015a) found that the radiation from the giant corresponds to its effective temperature T ef f = 3800 − 4000 K, and the radius Rg = (61 − 55)(d/1.6 kpc) R⊙. Comparing our spectra with spectra of red giants (Houdashelt et al 2000;Bagnulo et al 2003;Zhong et al 2015), we estimate a similar spectral type M2 III.…”
Section: Red Giantsupporting
confidence: 62%
“…Mondal et al (2018) from the absorption band indices derived the spectral type to be M2-M3. Skopal (2015a) found that the radiation from the giant corresponds to its effective temperature T ef f = 3800 − 4000 K, and the radius Rg = (61 − 55)(d/1.6 kpc) R⊙. Comparing our spectra with spectra of red giants (Houdashelt et al 2000;Bagnulo et al 2003;Zhong et al 2015), we estimate a similar spectral type M2 III.…”
Section: Red Giantsupporting
confidence: 62%
“…7). The photosphere fit of 2006 eruption [66], when rescaled to the nova distance of 2.45 kpc, provides a similar radius (245 − 310) R , and temperature (8200 K).…”
Section: B3 Optical Photometrymentioning
confidence: 91%
“…Filled markers show the flux after subtraction of Hα and Hβ line contributions. The thick black lines show a black-body emission used in the modeling, while the dashed line shows for comparison the average 2006 spectral fit from[66] (with the photosphere radius corrected to the distance of 2.45 kpc).…”
mentioning
confidence: 99%
“…Completeness. A cursory examination of the Two Micron All Sky Survey (2MASS) and Skiff catalogs (Cutri et al 2003a;Skiff 2014) can give an indication of the completeness of our giant star sample. First, the 2MASS catalog was sampled for all objects brighter than K < 3.5, resulting in approximately 13,000 objects.…”
Section: Target Selection For Ptimentioning
confidence: 99%
“…Calibration of "canonical" values for temperature and radius has wide-ranging utility in astrophysics. Evaluation of X-ray transient host stars (Skopal 2015;McCollum et al 2018), interpretation of protoplanetary environments (Arulanantham et al 2017), establishing the temperature of a galactic runaway giant (Massey et al 2018), and modeling of galactic longperiod variables (Barthès & Luri 2001) are a few examples of the use of our earlier calibration of effective temperature (van Belle et al 1999, hereafter vB99). Improved temperature calibrations can have wide-ranging effects, particularly when they refine calibrations used in large surveys (e.g., the symbiotic star survey of Akras et al 2019).…”
Section: Introductionmentioning
confidence: 99%